IRELAND’S RELATIONSHIP TO THE BRITISH EMPIRE FROM COLONIALISM IN THE SIXTEENTH CENTURY TO POSTCOLONIALISM IN THE TWENTIETH CENTURY: AN HISTORICAL AND LITERARY APPROACH - Lima, Geraldo Ferreira de (fólio - Revista de Letras, 2018)
Ireland’s relationship to the British Empire has been considered something either confusing or controversial. According to Stephen Howe “most historians would concur that the history of modern Ireland has been associated with that of the British Empire”(HOWE, 2002, p. 220). In 1541, Ireland was granted the status of Kingdom. The Act of Union made Ireland “an equal partner in the United Kingdom”. However, from the Glorious Revolution on, the Irish Protestant Ascendancy look inside themselves and what they see is a country which is “a ‘sister kingdom’ to England and Scotland”. English politicians by their turn are not able to see anything more than “a depending kingdom, a foreign country or a child-colony”. Supported by historical and literary approaches related to colonialism and postcolonialism, this work tries to demonstrate how ambiguous has been such relationship.